My say : Gold still glitters - Mydin Meera, Ahamed Kameel (The Edge, 2010)
In recent week,arguments have raged about the fact that gold was ideal money in the past and thatit can no longer be an attractive investment for the long term.Nonetheless,i believe gold is still ideal money althought its role as money was stripped after the collapse of Bretton Woods in 1971